2013
DOI: 10.4236/ojms.2013.31002
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Condition, Growth and Reproduction of Hake, <i>Merluccius merluccius</i> L., in the Portuguese Coast

Abstract: Weight/length relationships, condition factor, gonadosomatic and hepatosomatic indices, conversion factor for gutted to total weight and spawning season of hake in the Portuguese Coast (36.92 to 42.22 degrees latitude N; 9.61 to 6.07 degrees longitude W) were investigated for the first time, aiming to fill the lack of information on the biology of hake of the Portuguese waters. Data were obtained from commercial samples collected between 2005 and 2010 and pooled by month. Sex ratio observed in fish below 40 cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 26 publications
(15 reference statements)
1
17
1
1
Order By: Relevance
“…It is obvious from Table 6 that, M. merluccius in the present study in the Egyptian Mediterranean waters shows no significant differences with Abd El Aziz (1976) and Soliman (1992) in the same region, while this species in the present study was less heavier than those reported in Bay of Biscay (Ices, 1991;Lucio et al, 2000), Iberian Atlantic (Pineiro and Sainza, 2003), Moroccan (Belcaid and Ahmed, 2011), and in Portuguese coast (Costa, 2013). These variations in different regions (Table 6) can be attributed to different conditions of food and temperature prevailing in these areas (Bruton, 1990) and water temperature can also affect fish growth directly by affecting the physiology of the fish (Weatherly and Gills, 1987).…”
Section: Discussioncontrasting
confidence: 70%
“…It is obvious from Table 6 that, M. merluccius in the present study in the Egyptian Mediterranean waters shows no significant differences with Abd El Aziz (1976) and Soliman (1992) in the same region, while this species in the present study was less heavier than those reported in Bay of Biscay (Ices, 1991;Lucio et al, 2000), Iberian Atlantic (Pineiro and Sainza, 2003), Moroccan (Belcaid and Ahmed, 2011), and in Portuguese coast (Costa, 2013). These variations in different regions (Table 6) can be attributed to different conditions of food and temperature prevailing in these areas (Bruton, 1990) and water temperature can also affect fish growth directly by affecting the physiology of the fish (Weatherly and Gills, 1987).…”
Section: Discussioncontrasting
confidence: 70%
“…Likewise, temporal variation in growth (Domínguez-Petit et al, 2008), skipped spawning and changes in the proportion of immature/mature fish resulting from varying migration intensities, could influence the observed L 50 . The presence of very large hake, some over 100 cm in length, may also explain the high GSI values recorded in July, since larger fish tend to have disproportionally heavier gonads than smaller individuals (Lucio et al, 1998;Costa, 2013). Reproductive indices show that spawning activity is likely to be concentrated during those months with a higher presence of large and mature individuals.…”
Section: Locationmentioning
confidence: 93%
“…There is usually good correspondence between macroscopic maturity staging and GSI Costa, 2013), although the coarse resolution of the maturity stages can result in a wide range of GSI values. Hake are serial spawners, and females can release up to 10 batches of eggs (ova) at approximately 5-10 day intervals over a period of several months in the Bay of Bis- Table 2 Size of maturation (L50; length at which 50% of the population reaches maturity) for males and females of European hake in its different areas of distribution.…”
Section: Reproductive Indicesmentioning
confidence: 96%
See 1 more Smart Citation
“…Hence, large variations in proximate composition of fish species reflects physiological processes and changes in environmental conditions that together dictate spawning, migration, and starvation or heavy feeding activities (Boran & Karaçam, 2011;Costa, 2013).…”
Section: Discussionmentioning
confidence: 99%